Telaah Pentingnya Masjid dan Perannya dalam Islam Menurut Al-Imam Khomiini dalam Kitab al-Masjid Ahmiyatahu Wadu>rohu fi> al-Isla>m - Widodo, Widodo; Basuki, Basuki (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
Muslims often use mosques as centers of activity. The mosque being the axis of Islamic activities is very appropriate to be implemented in society, apart from being used for worship, it can also be used as a basis for society in life. This article explains the study of the importance of mosques and their role in Islam according to Al-Imam Khomiini in the book al-Masjid Ahmiyatahu Wadu>rohu fi> al-Isla>m. The primary data source in this research comes from the book al-Masjid Ahmiyatahu Wadu>rohu fi> al-Isla>m. Using secondary sources of information from books and articles relevant to the research theme through documentation techniques is a common and effective approach in research. Documentation techniques involve collecting data from various existing documents and literature. Then in content analysis, this research found the role of mosques according to Al-Imam Khomiini, namely: (1) mosques as the axis of Islamic activities (2) mosques as places of worship (3) mosques as a place to educate the next generation (4) mosque in building society. The results of the research show that mosques have a significant role in community life such as centers of worship, education centers, economic centers for the people, centers of social activities, and centers for the benefit of the people in Islamic society.